IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BIOLOGI - Yulia Ratna Sari; Yoko Masna Rivan (LPPM Universitas Cipta Mandiri, 2024)
Education is a very important thing to develop, especially character education. Character education is education that can form good moral, character, character or personality qualities in students. In implementing character education, the role of the teacher is very important, because teachers as examples and teachers must also instill the values ​​of character education by providing information about things that can shape good student character. This research aims to see how the character education of students is implemented in high school, especially in biology learning. The method used in this research is a literature review. The reading sources used are relevant international and national articles. This data analysis technique is carried out in a descriptive manner by analyzing and identifying the reading sources obtained so as to produce a very informative summary. Based on the results of the literature analysis, it is known that in implementing character education in high school in biology learning, biology teachers implement character education by creating a design of character education values ​​which has been attached to the Learning Implementation Plan (RPP) and implementing it in the learning process through conveying messages and words. The values ​​applied include discipline, curiosity, love of reading, religion, cooperation and a sense of responsibility. With this character education, it is hoped that it can form students who have good morals, character and personality.